PERSEPSI SISWA DALAM PEMBELAJARAN SENI TARI DI SMP NEGERI 11 SIJUNJUNG - Islamia, Raudhatan; Susmiarti, Susmiarti; Astuti, Fuji (FBS Universitas Negeri Padang, 2019)
AbstractThis article aims to describe the perceptions of students in pembelejaran dance in SMP N 11 Sijunjung. This type of research is a qualitative approach using descriptive. The population in this research is grade VIII as many as 170 people. Sampling 42 students using the technique of sampling considerations (purposive) and random (random). Research instrument this is now about the student perception indicators i.e., acceptance and evaluation in learning the art of dance in SMP N 11 Sijunjung. Data collection is carried out through quantitative techniques the percentages and then processed into the qualitative data in the form of a descriptive. The results showed that the perception of students SMP N 11 Sijunjung already included into both criteria, can be seen from the overall perception of students which includes acceptance and evaluation in learning the art of dance has been reach 70.30%. From the results of the assessment, 73.81% of students give a good response, the next pass judgement 66.79% of students in both subjects the art of dance. Based on the results of the analysis it can be concluded that the percentage of the perception of students in learning the art of dance in SMP N 11 Sijunjung obtained 70.30% which belongs either.Keywords: perception of students, dance